Research on drug resistance mechanism of trastuzumab caused by the activation of PI3K/Akt signaling pathway - Chen, Xi; Wang, Han; Ou-yang, Xue-nong; Xie, Fang-wei; Wu, Jing-jing (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: To discuss the activation of the signal transduction pathway of phosphatidylinositol 3’-kinase/serine-threonine kinase (PI3K/Akt), one of the important targets of drug resistance of trastuzumab, which provides a theoretical basis for the targeted therapy of drug resistance of trastuzumab in breast cancer. Material and methods: Establish the drug-resistance sub-strain BT-HerR of trastuzumab for the continuous treatment of human breast cancer cell strain BT474, conduct Her-2 phenotype analysis on the drug-resistance cell strain BT-HerR with the FISH method, detect the proliferation inhibition in vitro of trastuzumab to BT474 and BT-HerR cells with the MTT method, detect the apoptosis variation after interference of trastuzumab with a flow cytometer and detect p-Akt and apoptosis-related protein expression with Western blot after PI3K/Akt inhibitor LY294002 interferes with the cells. Results : The gene expression of drug-resistance cell strain BT-HerR Her-2 is strongly positive; 72 hours after interference of trastuzumab, the proliferation in vitro of the BT474 and BT-HerR cells is inhibited, which is strengthened with the increase of concentration, showing a significant difference (p < 0.01); after treatment of trastuzumab, comparison of the cell apoptosis rate of BT474 and BT-HerR shows a significant difference (p < 0.01); trastuzumab can only inhibit the Akt protein phosphorylation of BT474, while LY294002 can inhibit the BT-HerR and BT474 Akt protein phosphorylation simultaneously. Conclusions : Akt protein phosphorylation of trastuzumab drug-resistance cells is activated; LY294002, a PI3K/Akt inhibitor, can obviously inhibit Akt protein phosphorylation of trastuzumab drug-resistance cells and there is a clear association between the PI3K/Akt signal transduction pathway and trastuzumab resistance.